THE IMPACT OF SMALL ARMS ON CHILDREN AND GIRLS IN ARMED CONFLICTS. - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The use of arms whether small, light, improvised or weapons of mass destruction in conflict, is not new; and this explains why the right of self-defence and self determination are part of the international law. What is rather new is that access to these weapons is easy and cheap. Records have it that you can exchange an AK47 for as little as a bag of grain, and studies have it that, there are more arms with the militias than in the National armies of most African countries. And what is most unacceptable is the indiscriminate use of these weapons, against those that the humanitarian laws are out to protect. The proliferation of these weapons in the hands of undisciplined actors has outpaced the efforts to ensure compliance with the basic rules of warfare. The aftermath is levels of wanton violence and streams of horrific images.